2015
DOI: 10.4236/ojms.2015.54032
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Chitinolytic Enzymes in the Organs and cDNA Cloning of Chitinase Isozymes from the Stomach of Two Species of Fish, Chub Mackerel (<i>Scomber japonicus</i>) and Silver Croaker (<i>Pennahia argentata</i>)

Abstract: Chitinolytic activities were measured in two fish species having different feeding habits, chub mackerel (Scomber japonicus) and silver croaker (Pennahia argentata). Chitinase (an endo-type chitinolytic enzyme) activity was measured using pNP-(GlcNAc)n (n = 2, 3) as substrates; its level was significantly high in the stomachs of both species, as well as in the gills, intestine, pyloric appendage, testis, and liver of chub mackerel and in the spleen, kidney, pyloric appendage, ovaries, heart, and liver of silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In contrast, DkChi was expressed in all organs of D. kwangtungensis, but chitinase activity was observed only in the stomach, and based on the feeding status of the three samples used in the current study, the possibility of adjustment for expression confined to the stomach exists. Conversely, Hex activity, which was measured using pNP-GlcNAc as the substrate, was detected in all organs, similar to previous reports [11] …”
Section: Glycoside Family 18 Catalytic Domainsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, DkChi was expressed in all organs of D. kwangtungensis, but chitinase activity was observed only in the stomach, and based on the feeding status of the three samples used in the current study, the possibility of adjustment for expression confined to the stomach exists. Conversely, Hex activity, which was measured using pNP-GlcNAc as the substrate, was detected in all organs, similar to previous reports [11] …”
Section: Glycoside Family 18 Catalytic Domainsupporting
confidence: 73%
“…Two varieties of the chitinase genes were obtained from the stomach of the fish and subjected to phylogenetic analysis, based on the deduced amino acid sequence 2 fish-specific groups, acidic fish chitinase-1 (AFCase-1) and acidic fish chitinase-2 (AFCase-2) were identified [6]. In addition, chitinase activity has been observed in organs, excluding the stomach, in the class of fish classified as Actinopterygii [11] [12], and a new group fish chitinase-3 (FCase-3), has been identified based on an isoform found in the stomach and kidneys [12]. In contrast, not even one chitinase gene of the AFCase-1, AFCase-2, and FCase-3 groups has been detected in the stomach of either Prionace glauca, classified as a Chondrichthyes, or the stomach of Latimeria chalmnae, classified as Sarcoptery-…”
Section: Introductionmentioning
confidence: 99%
“…in digestive organs has been thought to play a role in the degradation of (GlcNAc) n into GlcNAc, produced via the effect of chitinases in the stomach [31]. It has been reported that fish contain chitinous substances in their scales [33], have chitin synthases [34], and have a mechanism of carbohydrate metabolism [35].…”
Section: Distribution Of Chitinolytic Enzymementioning
confidence: 99%
“…Furthermore, in fish, chitinase activity has been M. Watanabe et al DOI: 10.4236/abb.2018. 91004 38 Advances in Bioscience and Biotechnology observed not only in the digestive tract, but also in other organs [31]. Also, an acidic mammalian chitinase (AMCase) was found in mammals, which are vertebrates like fish, and this AMCase is involved in digestion and absorption of food [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chitinases in the fish stomach are classified into two groups based on differences in their primary structure and the patterns of degradation of (GlcNAc) n : acidic fish chitinase-1 (AFCase-1) and acidic fish chitinase-2 (AFCase-2) [16] [17] [18] [19]. Conversely, studies reporting the cDNA cloning and expression of chitinases and chitinase-like proteins from bivalves and gastropods, which are mollusks, have noted that these play roles in shell formation [20] [21] [22], immunity [23] [24] [25] [26], and digestion [27].…”
Section: Introductionmentioning
confidence: 99%